ESOP fables: The impact of employee stock ownership plans on labor disputes - Peter Cramton; Hamid Mehran; Joseph Tracy (Federal Reserve Bank of New York, 2008)
By the early 1990s, employee stock ownership plans (ESOPs) had become as prevalent in unionized firms as in nonunionized firms. However, little research has been devoted to examining the implications of ESOPs for collective bargaining or, more generally, for cross ownership. In this paper, we extend the signaling model of Cramton and Tracy (1992) to allow partial ownership by the union. We demonstrate that ESOPs create incentives for unions to become weaker bargainers. As a result, the model predicts that ESOPs will lead to a reduction in strike incidence and in the fraction of labor disputes that involve a strike. We examine these predictions using U.S. bargaining data from 1970 to 1995. The data suggest that ESOPs do increase the efficiency of labor negotiations by shifting the composition of disputes away from costly strikes. Consistent with improved bargaining efficiency, we find that the announcement of a union ESOP leads to a 50 percent larger stock market reaction when compared with the announcement of a nonunion ESOP.
Keywords: J52; C78; D82; 330; Collective bargaining; ESOP; cross ownership; incomplete information; strikes; labor disputes; Lohnverhandlungen; Tarifpolitik; Mitarbeiterkapitalbeteiligung; Arbeitskonflikt; Streik; USA